Relationship between net photosynthetic rate of flue-cured tobacco and its physio-ecological factors - ZHANG Guang-fu; ZHAO Ming-qin; HAN Fu-gen; LÜ Zhong-xian; LIU Le; YAN Yong-sheng (浙江大学学报. 农业与生命科学版)
The diurnal changes of net photosynthetic rate (Pn) in leaves of tobacco cultivar Jiyan NO. 9" were studied by LI-6400 portable photosynthesis system, and the relationship between the Pn and its physio-ecological factors was studied by principal components and path analysis. The results showed that the curve of diurnal variation of Pn was demonstrated single peak in clear day, and the majority of peak presented to 11:00, which was 9.88 μmol·m-2·s-1, and it did not show midday depression; the diurnal changes of stomatal conductance (Gs), transpiration rates (Tr), leaf temperature (TL) and air temperature (Ta) all appeared as single peak curves, and there were positive relationships between Gs, Tr, TL, Ta and Pn; TL and Tr were the major ones in diurnal change of physiological factors, and TL, Ta and Ca were the major ones in diurnal change of ecological factors; the direct impact of physiological factors to Pn was the order of Gs>TL>Tr>Ci, and the direct impact of ecological factors to Pn was the order of TL>Ta> relative humidity (RH) >Ca> photosynthetically active radiation (PAR). Comprehensive analysis showed that Gs, Tr and TL played very important roles in the changes of Pn among the physiological factors, and light and temperature affected the changes of Pn among the ecological factors.